Research progress of network-based interventions on self-care ability of patients with chronic heart failure (慢性心力衰竭患者自我护理能力网络干预的研究进展) - ZHAI Kaijing (翟凯静); ZHANG Yuqing (张雨晴); LIU Wei (刘薇); QIAO Zhihui (乔志桧); FANG Cui (方璀); FU Conghan (付聪晗) (中西医结合护理)
Chronic heart failure is a common chronic disease that has a significant impact on patients' quality of life and health. The ability to self-care plays a vital role in the management of patients with chronic heart failure. This study reviewed the recent researches on network-based interventions on self-care ability of patients with chronic heart failure, focusing on the effects of different network-based interventions on improving patients' self-care ability, enhancing symptom management and promoting mental health. The aim of this study is to ensure that these interventions meet the needs of different individuals to optimize the self-care management of chronic heart failure. (慢性心力衰竭是一种常见的慢性疾病, 严重影响患者的健康和生活质量。自我护理能力在慢性心力衰竭患者的健康管理中发挥着至关重要的作用。本研究综述了近年来关于慢性心力衰竭患者自我护理能力网络干预的研究进展, 重点分析了不同网络干预形式在提高患者自我护理能力、改善症状管理及促进心理健康方面的效果, 为提高慢性心力衰竭患者的自我护理能力提供有效的途径和方法。)